Upaya Meningkatkan Kreativitas Guru dalam Pengelolaan Pembelajaran Melalui Strategi Cooperative Cycle of Learning di SMP Harapan Kasih Kota Bandung - Ios Susila Nugraha (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to increase teacher creativity with the cooperative cycle learning strategy at Harapan Kasih Middle School. This research method uses school action research with quantitative data. Observations and assessments were carried out by the principal of the teachers at SMP Harapan Kasih with a total of 20 teachers who were the subject of observation. The implementation process goes through three phases, namely pre-cycle, cycle 1 and cycle 2. Action research in each cycle uses four stages, namely planning, action, observing and reflecting. The results showed that the cooperative cycle learning strategy could increase teacher creativity at Harapan Kasih Middle School. The average value of pre-action teacher creativity at Harapan Kasih Middle School was 39.7%, which is in the very low category. The average value of teacher creativity in cycle 1 was 63.8% in the sufficient category while the average value of teacher creativity at Harapan Kasih Middle School in cycle 2 was 86.7%. The results of the implementation of cycle 2 showed the success of the cooperative cycle learning strategy as an effort to increase teacher creativity at Harapan Kasih Middle School, Bandung City.